2004
DOI: 10.1023/b:jofl.0000031823.04926.75
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Enhancements on Silver Colloid Coated Surfaces

Abstract: We observed a strong, more than 16-fold, enhancement of Texas Red-labeled BSA fluorescence emission when deposited on silver colloid coated surfaces (SCCS). The same labeled protein deposited on silver island films (SIFs) showed an approximate 8-fold fluorescence enhancement. The lifetimes of Texas Red-BSA fluorescence are significantly shorter on silvered surfaces than on uncoated quartz substrate indicating a strong change in radiative decay rate of the dyes. We also observed a 36-fold increased brightness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…As expected, no difference in the emission spectra was detected. This is consistent with earlier results using Texas red-labeled bovine serum albumin [35]. The intensity of fluorescence at 575 nm was enhanced 4 times.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…As expected, no difference in the emission spectra was detected. This is consistent with earlier results using Texas red-labeled bovine serum albumin [35]. The intensity of fluorescence at 575 nm was enhanced 4 times.…”
supporting
confidence: 93%
“…The observed increase of brightness can be caused by the (i) increase of rhodamine quantum yield, (ii) the decrease in self-quenching [38], or (iii) the enhancement of the local electromagnetic field [35].…”
Section: Discussionmentioning
confidence: 99%
“…19). The signal on SCCS is almost twice as strong as that on SIFs [67]. Next, we measured life-times and again found that the intensity decays on SCCS are more affected than on SIFs (Fig.…”
Section: Comparison Of Fluorescence Enhancements On Sifs and Sccsmentioning
confidence: 76%
“…3-aminopropyltriethoxysilane (APS) was obtained from Fluka. The silver colloids used in these experiments were prepared by chemical reduction of silver nitrate with trisodium citrate using a modified Lee and Meisel method [21][22][23]. According to this method the sodium citrate first acts as a reducing agent, and later the negative citrate ions are adsorbed on silver nanoparticles.…”
Section: Methodsmentioning
confidence: 99%